Effective Singlet Oxygen Generation in Silica‐Coated CsPbBr3 Quantum Dots through Energy Transfer for Photocatalysis. Issue 4 (21st January 2020) - Gu, Kailun; Wang, Yu; Shen, Jianhua; Zhu, Jingrun; Zhu, Yihua; Li, Chunzhong
Abstract: Here, silica‐coated CsPbBr3 quantum dots (QDs) were demonstrated to be effective photosensitizers for the generation of singlet oxygen ( 1 O2 ). The silica encapsulation improved the stability of the perovskite QDs while also preserving an excellent light‐harvesting capability in the visible‐light region. The appropriate exciton binding energy and dark exciton generation characteristics of perovskite QDs may be responsible for the energy transfer. The high oxidizability of 1 O2 makes the material attractive for application in decomposition of organic dyes such as methyl orange. This work provides new insight for designing excellent perovskite‐based photocatalysts. Abstract : Get excited : Silica‐coated CsPbBr3 quantum dots are used as effective photosensitizers for the generation of singlet oxygen ( 1 O2 ). Silica encapsulation maintains the desirable phase and morphology of perovskite quantum dots during photocatalysis, improving the stability while also preserving an excellent light‐harvesting capability in the visible‐light region.